Fluffy cuffs: SME's innovation in alliances with buyer firms - Ricarda B. Bouncken; Martin Ratzmann; Jeffrey G. Covin (Small Business Economics, 2023)
Supplier firms, especially the more resource constraint SMEs, form alliances for product innovation. Supplier firms can try to push in creative inputs while needing to align them with the overall solution of the buyer. Our study zooms in on this push and alignment balancing act. Our theoretical model is informed by the attention-based view. It considers two centralization mechanisms, relationship intensity and formalized specifications of the buyer firm. Our dependent variable is innovation of the SME supplier. The model hypothesizes linear and non-linear effects by relationship intensity and the buyer's detailed and formalized specifications (e.g., functional principles, features, and design elements). Data collected from 279 European supplier SMEs reveals that moderate levels of "post-formational specifications" proposed by the buyer firm are associated with greater product innovation of the supplier. Interestingly, less product innovation results when the specifications of the buyer are either minimal or high. Stronger relationship intensity allows greater product innovation as it enables partners to capture more benefits from the post-formational specifications as they constructively work together.
Keywords: M10; O31; C12; C30; C83; D22; 330; SME; SME supplier firms; Product development alliances; Post-formational specifications; Innovation